Alat Bukti dalam Perkara Sengketa Waris - Nisa Ul Zakiyah; Fauziah Lubis; Hanita Pratiwi; Yulia Sari Devi Siregar; Sindi Awwaliyyah Lingga; Fadly Anhar Gultom (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the types of evidence used in inheritance cases and to assess their probative value based on the provisions of civil procedural law in Indonesia. Inheritance disputes are among the most complex matters in Indonesian civil law, involving not only the question of who is entitled to inherit but also the evidence used to prove such rights in court. This article discusses the various types of evidence used in inheritance cases, including documentary evidence, witness testimony, presumptions, confessions, oaths, and electronic evidence. The research employs a normative juridical approach and case studies. The findings indicate that understanding the types and probative value of evidence is crucial to the success of inheritance claims. This study is expected to enhance the understanding of civil procedural law in the context of inheritance litigation.